# Friday September 27 **Last time:** We saw $\Phi \subseteq \lieh^* = \theset{\alpha: \lieh \to \CC}$. Suppose $\lieg$ is semisimple and $\lieh$ is a maximal toral subalgebra and take $F = \CC$. **Propositions:** a. $\dim \lieg_\alpha = 1 ~\forall \alpha \in \Phi$ b. $\CC \alpha \intersect \Phi = \theset{\pm \alpha}$, and $2\alpha \not\in\Phi$ where $c\alpha: \lieh \to \CC,~ h \mapsto c\actson \alpha(h)$. Moreover, $M = \lieh \oplus \left( \bigoplus_{c\neq0} \lieg_{c\alpha} \right)$ c. If $\alpha, \beta \in \Phi$ and $\beta \neq -\alpha$ Let $p,q \in \ZZ$ be the largest such that $\beta -p\alpha$ and $b + q\alpha$ are in $\Phi$. Moreover, $\beta(h_\alpha) = \kappa(t_\beta, t_\alpha) = p-q \in \ZZ$. *Proof of (c):* Set $M = \sum_{i\in \ZZ} \lieg_{\beta + i\alpha}$, which is an $\liesl(2, \alpha)$ module. By (a), we have $\dim \lieg_{\beta + i\alpha} = 1 \iff \beta + i\alpha \in \Phi$. But for all $x\in \lieg_{\beta + i\alpha}$, we have $[h, x] = (\beta + i\alpha)(h)x$ for all $h\in\lieh$. But then $[h_\alpha, x] = (\beta(h_\alpha) + i \alpha(h_\alpha))x = (\beta(h_\alpha) + 2i)x$ Then $\lieg_{\beta + i\alpha} \subseteq M_{\beta(h_\alpha) + 2i}$, so $\beta(h_\alpha) \in \ZZ$. Moreover, $\mathrm{Wt}(M) = 2\ZZ$ or $2\ZZ + 1$, and in particular $\dim M_0 + \dim M_1 = 1$. Thus $M$ is irreducible, and $M \cong L(m)$ for some $m \in \ZZ_{\geq 0}$. Moreover, $\mathrm{Wt}(M) = \theset{m, m-2, \cdots -m}$, and$simg \lieg_{\beta + i\alpha} = 1$ for all $i \in [-p, q]$. Thus $\beta + i\alpha \in \Phi$. *Proof of 8.3(e):* $\alpha(t_\alpha) \neq 0$. The claim is that for all $\beta \in Phi$, there exists an $r\in \QQ$ such that $\beta(h) = r\alpha(h)$ for all $h \in [\lieg_\alpha, \lieg_{-\alpha}]$. There are two cases: if $\beta = -\alpha$, then we're done by the previous argument. Otherwise, $\beta \neq -\alpha$. Take $M = \bigoplus_{i \in\ZZ} \lieg_{\beta + i\alpha}$. Then, \begin{align*} \Tr_M(\ad h) &= \sum_i \Tr_M( (\ad e_i \circ \ad f_i) -(\ad f_i \circ \ad e_i) ) \\ &= \sum_i \Tr_{\lieg_{\beta + i\alpha}}(\ad h) \\ &= \sum (\beta + i\alpha)(h) \dim \lieg_{\beta + i\alpha} \\ &= \sum_i \dim \lieg_{\beta + i\alpha} \beta(h) + \sum_i i\dim(\lieg_{\beta + i\alpha}) \\ \implies \beta(h) &= \frac{ -\sum_i \dim \lieg_{\beta + i\alpha} }{ \sum_i \dim \lieg_{\beta + i\alpha} }\alpha(h) .\end{align*} Now consider the killing form $\kappa(t_\beta, t_\alpha) = \beta(t_\alpha) = r \alpha(t_\alpha)$, where the last equality is what we are claiming. Suppose that $\alpha(t_\alpha) = 0$. Then $\kappa(t_\beta, t_\alpha) = 0$ for all $\beta \in Phi$. By the non-degeneracy of $\kappa$, we have $t_\alpha = 0$ and thus $\alpha = 0$. ## Summary We have $\lieg$ semisimple, finite dimensional, and $\lieh$ a maximal toral subalgebra (i.e. the Cartan subalgebra). This implies that $\kappa$ is nondegenerate, and we have a correspondence \begin{align*} \lieh \iff \lieh\dual \\ h \mapsto \kappa(h, \wait) \\ t_\alpha \leftarrow \alpha .\end{align*} This gives a symmetric bilinear form $(\wait, \wait): \lieh\dual \to \lieh\dual$. For $\alpha \in Phi$, define its *coroot* $\alpha\dual = \frac{2}{(\alpha, \alpha)}\alpha$. Note that $(\wait)\dual$ is not linear: note that \begin{align*} (2\alpha)\dual = \frac{2}{(2\alpha, 2\alpha)} 2\alpha = \frac{\alpha}{(\alpha, \alpha)} = \frac{\alpha\dual}{2} .\end{align*} Assume that $\Phi = \theset{\alpha_i}$. Define $E_\QQ = \bigoplus_{i=1}^\ell \QQ_{\alpha_i}$, and $E = \RR \tensor_\QQ E_\QQ$. **Lemma:** If $\alpha, \beta \in \Phi$, then a. $(\beta, \alpha) \in \QQ$, b. $(\wait, \wait)$ on $E_\QQ$ is positive definite, i.e. $x\neq 0 \implies (x, x) > 0$. An immediate consequence of (b) is that $(\wait, wait)$ on $E$ is an inner product. *Proof:* For all $\lambda, \mu \in \lieh\dual$, we have \begin{align*} (\lambda, \mu) &= \kappa(t_\lambda, t_\mu) \\ &= \Tr_\lieg(\ad t_\lambda \circ \ad t_\mu) \\ &= \Tr_\lieg(...) + \sum_{\alpha \in \Phi} \Tr_{\lieg_\alpha}(...) \\ &= 0 + \sum_{\alpha \in \Phi} \alpha(t_\lambda) \alpha(t_\mu) \\ &= \sum_[\alpha \in \Phi] = \kappa(t_\alpha, t_\lambda) \kappa(t_\alpha, t_\mu) \\ &= \sum_{\alpha \in \Phi} (\alpha, \lambda)(\alpha, \mu) \\ .\end{align*} So pick $\lambda = \mu = \alpha \in \Phi$. Then $(\alpha, \alpha) = \sum_{\beta \in \Phi} (\beta, \alpha)^2$. Then \begin{align*} \frac{1}{(\alpha, \alpha)} = \sum_{\beta \in \Phi} \left(\frac{(\beta, \alpha\dual)}{2} \right)^2 .\end{align*} where $(\beta, \alpha\dual) = \cdots = \beta(h_\alpha)\in \ZZ$. This means that $(\alpha, \alpha) \in \QQ_{> 0}$. **Summary of Properties Proved:** Let $\alpha, \beta \in \Phi$. Then 1. $0 \not\in \Phi$ and $\Phi$ spans $E$ 2. $\CC\alpha \intersect \Phi = \theset{\pm \alpha}$ 3. $\beta - (\beta, \alpha\dual)\alpha \in \Phi$ 4. $(\beta, \alpha\dual) \in \ZZ$ Thus the assignment $(\lieg, \lieh) \mapsto (\Phi, E)$ defines a **root system**. This only works when $\lieg$ is semisimple and $\lieh$ is maximal toral. *Proof of (3):* We computed $(\beta, \alpha\dual) = p-q$. Then $-p \leq -(\beta, \alpha\dual) = q-p \leq q$. So this must be something on the root stream.